(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
This study was conducted to test the effect of season and breed on thermoregulatory parameters of three Nigerian indigenous breeds of cattle raised in Sudan Savanna Zone. A total number of nine (9) cattle aged between 4-5 years were used for this study. Data were taken for sixteen weeks across two seasons; Cold and Hot Season from three indigenous breed of cattle. Rectal temperature was recorded using digital thermometer, pulse rate was determined using stethoscope and respiratory rate was determined by counting of the respiratory movements of flank area. Data of ambient temperature and relative humidity were recorded on daily basis and temperature humidity index was calculated. All data obtained were subjected to analysis of variance using SAS software. Seasons significantly (P < 0.05) affect all the thermoregulatory parameters of with hot seasons having the highest values. Breed influenced (p<0.05) all the parameters measured. Red Bororo had the highest rectal temperature, while Sokoto has the least rectal temperature. Higher respiratory rate was recorded in SokotoGudali. Respiratory Rate of White Fulani are statistically similar with both Red Bororo and SokotoGudali, but Respiratory Rate of Red Bororo cattle has significantly difference (P<0.05) with SokotoGudali breeds of cattle. Pulse rate differs significantly (P<0.05), SokotoGudali recorded the highest rate and the least rate was observed in White Fulani cattle. It was concluded that Season affect all the thermoregulatory parameters and all the tested parameters were higher during hot season and SokotoGudali react more to thermal stress than Red Bororo and White Fulani